2016
DOI: 10.1186/s12916-016-0617-3
|View full text |Cite
|
Sign up to set email alerts
|

Human newborn bacille Calmette–Guérin vaccination and risk of tuberculosis disease: a case-control study

Abstract: BackgroundAn incomplete understanding of the immunological mechanisms underlying protection against tuberculosis (TB) hampers the development of new vaccines against TB. We aimed to define host correlates of prospective risk of TB disease following bacille Calmette–Guérin (BCG) vaccination.MethodsIn this study, 5,726 infants vaccinated with BCG at birth were enrolled. Host responses in blood collected at 10 weeks of age were compared between infants who developed pulmonary TB disease during 2 years of follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(59 citation statements)
references
References 34 publications
(48 reference statements)
6
53
0
Order By: Relevance
“…Extremes in the ratio of peripheral blood to monocyte lymphocytes were found to be associated with increased risk of TB in HIV infected adults in South Africa and suggested to be a tool to stratify risk of TB [36]. In a separate study in infants who received BCG vaccination at birth and had higher monocyte to T cell ratios, transcriptional profiles were associated with an activated macrophage phenotype likely involved in pathogenesis of risk of TB disease suggesting that a phenotype of activated monocytes may be detrimental to the host [37]. It is thus important to classify the monocyte subsets behind this IL-1β response in further studies as well as measure associated soluble markers of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Extremes in the ratio of peripheral blood to monocyte lymphocytes were found to be associated with increased risk of TB in HIV infected adults in South Africa and suggested to be a tool to stratify risk of TB [36]. In a separate study in infants who received BCG vaccination at birth and had higher monocyte to T cell ratios, transcriptional profiles were associated with an activated macrophage phenotype likely involved in pathogenesis of risk of TB disease suggesting that a phenotype of activated monocytes may be detrimental to the host [37]. It is thus important to classify the monocyte subsets behind this IL-1β response in further studies as well as measure associated soluble markers of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The need for improved 4 strategies to control childhood TB has led to studies to identify risk factors for 5 TB disease in children. The longitudinal data collected during infant TB vaccine 6 efficacy trials in South Africa with the vaccines BCG and Modified Vaccinia 7 Virus Ankara expressing Antigen 85A (MVA85A) 1,7 have enabled the 8 identification of correlates of TB disease risk in infants 3,8 . Using samples 9 collected at enrolment from infants into the MVA85A efficacy trial in the Western 10 Cape Province of South Africa 1 , we reported that CD4+ T-cell activation in 4-6 11 month old infants and adolescents, measured as HLA-DR expression, was 12 associated with increased risk of TB disease over the following 3 years of life 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Initial priming of the immune system upon first mycobacterial contact seems increasingly important. Gene expression analysis revealed that BCG vaccination in young infants induced two dichotomous responses, likely involving differential monocyte activation [76]. Similarly, dichotomous responses to primary BCG vaccination were also observed in adults [77].…”
Section: Protection Mediated By Trained Immunitymentioning
confidence: 90%